2003
DOI: 10.2320/matertrans.44.2701
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Diffusion Bonding of Silicon Nitride Using Vanadium Foils

Abstract: This paper describes the relation between the interfacial microstructure and the fracture strength of the joints of silicon nitride (Si 3 N 4 ) and vanadium (V) formed by solid state diffusion bonding. At first, the interfacial microstructure and its evolution process were analyzed in detail. The phase sequence at the interface changes with the bonding time showing five typical stages. In the first stage, a V 3 Si layer and V 2 N grains are formed. The V 2 N grains contact with the V 3 Si layer at 1473 K and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The chemical reactions at high temperatures between Si 3 N 4 and element V are complex so that different reaction products have been reported in some references under different experimental conditions . Maeda et al . reported that in the system of Si 3 N 4 –V–Si 3 N 4 under a bonding condition of 1473 K/60 min/140 MPa, not only V 3 Si but also V 2 N were formed at the interface, and with the increase of bonding temperature and the prolonging of bonding time, besides V 3 Si and V 2 N, new reaction products of V 5 Si 3 N 1−x and VN appeared in the joint.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical reactions at high temperatures between Si 3 N 4 and element V are complex so that different reaction products have been reported in some references under different experimental conditions . Maeda et al . reported that in the system of Si 3 N 4 –V–Si 3 N 4 under a bonding condition of 1473 K/60 min/140 MPa, not only V 3 Si but also V 2 N were formed at the interface, and with the increase of bonding temperature and the prolonging of bonding time, besides V 3 Si and V 2 N, new reaction products of V 5 Si 3 N 1−x and VN appeared in the joint.…”
Section: Resultsmentioning
confidence: 99%
“…The actual phase sequences at the bonding temperatures were verified on the basis of the Ti-Al-Si-C quaternary chemical potential diagram. The diagram describes the relation between the phase equilibria and the chemical potential of each constituent element [10], being suitable for describing phase sequences of diffusion-bonded interfaces [11,12]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the Si 3 N 4 /Si 3 N 4 joints with high thermal and oxidation resistance can be achieved by adding metals such as Au, Pd, Ni, and V into the filler alloys. [5][6][7] In this study, two Au-Ni-V metals in the form of foils were used as filler alloys for brazing Si 3 N 4 ceramic. The microstructure and mechanical properties of the Si 3 N 4 /Si 3 N 4 joint were studied, and the bonding mechanism was discussed with reference to the discovered phases in the joint and brazing parameters.…”
Section: Introductionmentioning
confidence: 99%